2019
DOI: 10.1089/acm.2018.0431
|View full text |Cite
|
Sign up to set email alerts
|

Whole Systems Within Whole Systems: The Oregon Health Plan's Expansion of Services for Back and Neck Pain

Abstract: Objectives: The authors employ a Whole Systems framework to explore implementation of new guidelines for back and neck pain in Oregon's Medicaid system. Whole Systems research is useful for understanding the relationship between complementary and integrative health care (CIH) and conventional health care systems in real-world clinical and practice settings. Design: Preliminary results are from an observational study designed to evaluate statewide implementation of CIH and other non-pharmacological treatments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A redesign of reimbursement policies is needed to expand coverage for nonpharmacologic treatments, and reduce or remove copayments and deductible costs. Recent examples of payment reform include Oregon Medicaid covering a range of nonpharmacologic approaches for painful musculoskeletal conditions, 33 and Medicare announced in January of 2020 that they will cover acupuncture for chronic LBP. 34,35 United Healthcare has started to roll out plans with $0 copays for first three visits to chiropractic care and physical therapy for LBP.…”
Section: Discussionmentioning
confidence: 99%
“…A redesign of reimbursement policies is needed to expand coverage for nonpharmacologic treatments, and reduce or remove copayments and deductible costs. Recent examples of payment reform include Oregon Medicaid covering a range of nonpharmacologic approaches for painful musculoskeletal conditions, 33 and Medicare announced in January of 2020 that they will cover acupuncture for chronic LBP. 34,35 United Healthcare has started to roll out plans with $0 copays for first three visits to chiropractic care and physical therapy for LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Bohm 17 Dorr and Townley 26 Eaves et al 24 Heyward et al 1 Bohm: back pain, joint pain, neck pain most common (private and public insurance coverage) 17 Dorr: chronic fatigue syndrome (FL), lower back pain with poor functional prognosis (OR), frequent emergency room visits (RI) for state Medicaid programs 26 Eaves: neck and back pain 24 Heyward: lower back pain (public and private insurance coverage) 1 CA: California; FL: Florida; RI: Rhode Island; OR: Oregon; HMO: health maintenance organization.…”
Section: Healthcare Setting Provider Type and Coveragementioning
confidence: 99%
“…The primary barriers reported by providers regarding insurance coverage for acupuncture included credentialing challenges and reimbursement difficulties, particularly for non-physicians. Licensed acupuncturists in the study by Eaves et al 24 identified challenges with credentialing, low reimbursement rates, obtaining reimbursement, and increased patient no-shows as barriers in the implementation of Oregon's Medicaid coverage for acupuncture. Parkman 20 identified physician discomfort with acupuncture and a lack of physician referrals as additional barriers.…”
Section: Barriers From the Provider And Patient Perspectivementioning
confidence: 99%
“… 51 The current opioid crisis has put pressure on policy makers to manage pain with effective non-opioid treatments, and examples of acupuncture reimbursement for lower-income, younger adults by Medicaid are emerging. 52 , 53 Some younger adults with private insurance already have an acupuncture benefit, e.g., Kaiser Permanente Washington covers acupuncture. 20 Once payment policies are in place in a wider range of plans, evidence-based dissemination strategies can inform health system leaders, PCPs, and patients about acupuncture’s appropriateness for LBP.…”
Section: Tailoring Dissemination Strategies For Younger and Older Adultsmentioning
confidence: 99%